Magnesium air battery electrolyte and magnesium air battery
Patent Information
- Application Number
- CN202211041559.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-08-29
AI Technical Summary
然而,镁负极的利用率仍处于较低水平
[0031]本申请能产生的有益效果包括:
Smart Images

Figure CN117673584B_ABST
Abstract
Description
Technical Field
[0001] This application relates to a magnesium-air battery electrolyte and a magnesium-air battery, belonging to the fields of electrolyte preparation and electrochemical technology. Background Technology
[0002] Magnesium-air batteries use oxygen from the air as the positive electrode active material and magnesium metal and its alloys as the negative electrode. They feature simple structure, inherent safety, low cost, and good discharge performance (theoretical voltage of 3.1V and energy density of 6.8 kWh / kg). -1 It has the advantages of [missing information - likely related to energy efficiency]. It has been used as an emergency backup power source and is expected to be applied in electric vehicles, portable power supplies, flexible wearable power supplies, etc. Magnesium anodes have a low density (1.74 g / cm³). -3 High theoretical capacity (2.2 Ah g) -1 Magnesium has the characteristics of a negative potential (2.37V vs. SHE). However, magnesium is an active metal and is easily corroded in commonly used NaCl aqueous electrolytes, which greatly reduces the utilization rate of magnesium anodes and leads to significant mass and energy losses.
[0003] Currently, alloying magnesium metal and adding corrosion inhibitors to aqueous solutions to passivate the magnesium anode surface are common methods to reduce hydrogen evolution corrosion (HEC) on magnesium anodes. However, the utilization rate of magnesium anodes remains low. The accumulation of corrosion product layers and passivation surface films leads to a decrease in battery voltage because they hinder direct contact between the magnesium anode surface and the electrolyte. Organic electrolytes are now widely used in highly active metal-based battery systems, either as solvents or additives, to suppress HEC side reactions. Wang et al. introduced dimethyl sulfoxide (DMSO) with a high Gutmann donor number (DN) to limit free water and reduce water activity, suppressing self-discharge and HEC corrosion of aluminum anodes in alkaline electrolytes. Based on the strong interaction between H2O and DMSO, Gao et al. suppressed the decomposition of solvated H2O in aqueous electrolytes by adding DMSO to ZnCl2-H2O. Summary of the Invention
[0004] The purpose of this application is to provide a magnesium-air battery electrolyte to avoid the shortcomings of the prior art.
[0005] According to one aspect of this application, a magnesium-air battery electrolyte is provided, wherein the magnesium-air battery electrolyte is a two-phase electrolyte, comprising an anolyte and a catholyte;
[0006] The anolyte is an organic electrolyte;
[0007] The cathode electrolyte is an inorganic electrolyte.
[0008] Optionally, the organic electrolyte includes an anolyte and solvent I.
[0009] Optionally, the anode electrolyte is a fluoroborate.
[0010] Optionally, the solvent is selected from at least one of dimethyl sulfoxide and N,N-dimethylformamide.
[0011] Optionally, the inorganic electrolyte includes a cathode electrolyte and solvent II;
[0012] The cathode electrolyte is selected from at least one of sodium chloride, potassium chloride, sodium sulfate, potassium sulfate, and sodium formate; the solvent II is water.
[0013] Optionally, the fluoroborate is selected from at least one of sodium fluoroborate, potassium fluoroborate, and ammonium fluoroborate.
[0014] Optionally, the mass concentration of the anolyte in the anolyte is 5% to 20%.
[0015] Optionally, the mass concentration of the anolyte in the anolyte is selected from any value of 5%, 8%, 10%, 15%, 20% or a range between any two of the above.
[0016] Optionally, the mass concentration of the cathode electrolyte in the cathode electrolyte is 2% to 15%.
[0017] Optionally, the mass concentration of the cathode electrolyte in the cathode electrolyte is selected from any value of 2%, 5%, 10%, 15% or a range between any two of the above points.
[0018] According to another aspect of this application, a magnesium-air battery is provided, the magnesium-air battery including an anode, a cathode and a separator for separating the anode and the cathode, wherein the cavity between the anode and the separator is filled with an anolyte and the cavity between the cathode and the separator is filled with a cathode electrolyte;
[0019] The anolyte is selected from the anolyte of the magnesium-air battery electrolyte described above.
[0020] The cathode electrolyte is selected from the cathode electrolyte of the magnesium-air battery described above.
[0021] Optionally, the anode is a magnesium alloy.
[0022] Optionally, the anode is selected from at least one of AZ61 magnesium alloy, AZ31 magnesium alloy, and AZ91 magnesium alloy.
[0023] Optionally, the cathode is selected from at least one of a porous air electrode supported on MnO2 / C catalyst, a porous air electrode supported on Ag / MnO2 catalyst, and a porous air electrode supported on MnO2 / carbon nanotubes.
[0024] Optionally, the membrane is selected from at least one of PVDF-SPEEK ion exchange membrane, Nafion 115, and polyaniline.
[0025] Optionally, the anode utilization rate of the magnesium-air battery is 60% to 80%.
[0026] Optionally, the anode utilization rate of the magnesium-air battery is selected from any value of 60%, 65%, 67%, 70%, 75%, 80% or a range between any two of the above points.
[0027] Optionally, the discharge voltage of the magnesium-air battery is 0.1–1.8V; the power density of the magnesium-air battery is 1.2 mW / cm³. -2 ~11.5mW cm -2 .
[0028] Optionally, the discharge voltage of the magnesium-air battery is selected from any value among 0.1V, 0.5V, 1.0V, 1.5V, and 1.8V, or a range between any two of the above values.
[0029] Optionally, the power density of the magnesium-air battery is selected from 1.2 mW cm⁻¹. -2 3.0mW cm -2 5.0mW cm -2 7.5mWcm -2 10mW cm -2 11.5mW cm -2 Any value in the range or any two points mentioned above.
[0030] This invention provides a magnesium-air battery using NaCl-H2O as the cathode electrolyte, AZ61 magnesium alloy as the anode, a self-made porous air electrode with MnO2 / C as the catalyst as the cathode, and a self-made PVDF-SPEEK ion exchange membrane as the separator. This invention uses DMSO or DMF as the anode electrolyte solution and NaBF4 or KBF4 as the anode electrolyte solute. In this invention, by using organic electrolytes such as NaBF4-DMSO as the anode electrolyte, hydrogen evolution corrosion of AZ61 magnesium alloy during discharge can be suppressed, thereby improving its discharge utilization rate. In this invention, by using NaCl-H2O as the cathode electrolyte, the cathode exhibits high discharge activity. Test results show that at 15 mA cm⁻¹… -2 At a current density of [value missing], the magnesium-air battery assembled with NaBF4-DMSO / NaCl-H2O as the electrolyte can still achieve a discharge voltage of 1.02V and a power density of 11.204 mW / cm². -2 At 1mAcm -2At current density, the utilization rate of AZ61 magnesium alloy reaches 67%, and the energy density of AZ61 magnesium alloy can reach 2020Wh / kg. -1 In a NaCl-H2O (10wt%) single electrolyte solution, the utilization rate of AZ61 magnesium alloy can only reach 50%, and its energy density is only 1617Wh / kg. -1 Its excellent electrochemical performance indicates that it has great application potential as an electrolyte for magnesium-air batteries. Furthermore, the preparation process of this electrolyte is simple and controllable, requiring only basic equipment, making it an easy method for large-scale production.
[0031] The beneficial effects that this application can produce include:
[0032] 1) The raw materials used in this invention are inexpensive materials such as sodium chloride (NaCl), sodium fluoroborate (NaBF4), potassium fluoroborate (KBF4), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF). These materials are widely available, green, safe, and inexpensive.
[0033] 2) The preparation method of this invention is simple and can be mass-produced.
[0034] 3) The biphase electrolyte obtained by this invention has a significant effect on suppressing the hydrogen evolution side reaction during the discharge of AZ61 magnesium alloy. Attached Figure Description
[0035] Figure 1 This is a schematic diagram of the novel NaBF4-DMSO / NaCl-H2O biphase electrolyte magnesium-air battery of this application.
[0036] Figure 2 For this application at 1mAcm -2 The discharge curves of a novel magnesium-air battery with NaBF4-DMSO / NaCl-H2O dual-phase electrolyte and a magnesium-air battery with NaCl-H2O single electrolyte were prepared at the specified current density.
[0037] Figure 3 For this application at 1mA cm -2 The anode utilization rate of the novel NaBF4-DMSO / NaCl-H2O biphase electrolyte magnesium-air battery prepared at a current density is shown in the figure.
[0038] Figure 4 For this application at 1mA cm -2 The anode energy density diagrams of the novel NaBF4-DMSO / NaCl-H2O biphase electrolyte magnesium-air battery prepared at the specified current density and the magnesium-air battery with NaCl-H2O single electrolyte are shown.
[0039] Figure 5This is a SEM image of the surface of the AZ61 magnesium alloy of this application after discharge in NaBF4-DMF electrolyte.
[0040] Figure 6 This is a SEM image of the surface of the AZ61 magnesium alloy of this application after discharge in NaCl-H2O electrolyte. Detailed Implementation
[0041] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0042] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0043] AZ61 was scanned using a JSM-7800F scanning electron microscope.
[0044] Electrochemical performance was tested using the Xinwei Battery Testing System.
[0045] This invention discloses a novel method for preparing a biphase magnesium-air battery electrolyte, comprising the following steps:
[0046] Weigh out the appropriate proportions of NaBF4 / KBF4, NaCl, DMSO / DMF, and deionized water. Dissolve NaBF4 and NaCl in DMSO and deionized water, respectively, and set aside for later use.
[0047] The novel biphase electrolyte system uses NaCl-H2O as the cathode electrolyte and NaBF4 / KBF4-DMSO / DMF as the anode electrolyte.
[0048] The mass concentration of NaBF4 / KBF4 is 5% to 20%, and the mass concentration of NaCl is 2% to 15%.
[0049] The prepared anolyte and catholyte were used in the above steps. A self-made PVDF-SPEEK ion exchange membrane was used as the separator, a self-made air electrode with MnO2 / C as the catalyst was used as the cathode, and AZ61 magnesium alloy was used as the anode to assemble a magnesium-air battery. The electrochemical performance of the prepared battery was then tested using the Xinwei Battery Testing System.
[0050] Preparation Example 1
[0051] The PVDF-SPEEK ion exchange membrane was prepared using a dissolution-regeneration method. Sulfonated polyetheretherketone (PEEK) and polyvinylidene fluoride (PVDF) were dissolved in an N,N-dimethylacetamide solution at a mass ratio of 9:1 and stirred for 1 hour. Then, the solution was coated onto a glass plate using a blade coating method and subsequently dried at 60°C for 1 hour to obtain the final membrane.
[0052] Preparation Example 2
[0053] The method for preparing a self-made air electrode using MnO2 / C supported catalyst is as follows: The MnO2 / C catalyst is prepared by a hydrothermal method. First, 3g of KMnO4 is dissolved in 60mL of deionized water, 6mL of anhydrous ethanol is added dropwise, followed by 0.8g of activated carbon. After stirring evenly, the mixture is transferred to a 100mL reaction vessel and kept at 130℃ for 24h. Then, it is allowed to cool naturally to room temperature. The brown precipitate is filtered, washed, and dried at 80℃ for 10h. Next, 1g of the prepared MnO2 / C catalyst is mixed with polytetrafluoroethylene (PTFE) emulsion (60% mass concentration) at a mass ratio of 7:3, and 1mL of deionized water is added and stirred for 1h. The mixed slurry is then brushed onto nickel foam with a catalyst loading of 10mg / cm³. -2 Subsequently, nickel foam coated with MnO2 / C catalyst was laminated together with a commercial diffusion layer to finally prepare a porous air cathode.
[0054] Example 1
[0055] Weigh out 8g of NaBF4, 10g of NaCl, 92g of DMSO and 90g of deionized water. Dissolve NaBF4 and NaCl in DMSO and deionized water respectively for later use.
[0056] The novel biphase electrolyte system uses NaCl-H2O as the cathode electrolyte and NaBF4-DMSO as the anode electrolyte.
[0057] The NaBF4 has a mass concentration of 8%, and the NaCl has a mass concentration of 10%.
[0058] like Figure 1 As shown, the anolyte and catholyte prepared according to the above steps were used as a separator with the PVDF-SPEEK ion exchange membrane prepared in Preparation Example 1, the air electrode with MnO2 / C catalyst prepared in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode to assemble a magnesium-air battery. The prepared battery was then subjected to electrochemical performance testing using the Xinwei Battery Testing System.
[0059] Figure 1 This is a schematic diagram of a novel magnesium-air battery designed with NaBF4-DMSO / NaCl-H2O two-phase electrolyte. It can be seen that the air cathode reacts in the NaCl-H2O electrolyte, with the reaction equation being O2 + 2H2O + 4e⁻. - →4OH - The AZ61 magnesium alloy anode undergoes a reaction in NaBF4-DMSO electrolyte, with the reaction equation being Mg - 2e⁻. - →Mg 2+ The designed magnesium-air battery uses a PVDF-SPEEK ion exchange membrane as the separator, which can transfer Na+ to the air. +Ions are conducted from the electrolyte on the anode side into the electrolyte on the cathode side, thereby connecting the circuit.
[0060] Figure 2 1mA cm -2 The discharge curves of a novel magnesium-air battery prepared with NaBF4-DMSO / NaCl-H2O dual-phase electrolyte and a magnesium-air battery prepared with NaCl-H2O single electrolyte are shown in Figure 2. It can be clearly seen from Figure 2 that the average discharge voltage of the battery in the prepared novel NaBF4-DMSO / NaCl-H2O dual-phase electrolyte is 1.37V (1.37mW cm⁻¹). -2 Slightly lower than the average discharge voltage of 1.42V (1.42mW cm⁻¹) of magnesium-air cells in NaCl-H₂O single electrolyte. -2 This is because the conductivity of NaBF4-DMSO electrolyte is lower than that of NaCl-H2O electrolyte.
[0061] Figure 3 1mA cm -2 The utilization rates of a novel magnesium-air battery prepared with NaBF4-DMSO / NaCl-H2O dual-phase electrolyte and a magnesium-air battery with NaCl-H2O single electrolyte are shown in the figure. Figure 4 1mA cm -2 The energy density diagrams of a novel magnesium-air battery with NaBF4-DMSO / NaCl-H2O dual-phase electrolyte and a magnesium-air battery with NaCl-H2O single electrolyte prepared at the specified current density are shown. Figure 3 and Figure 4 As can be seen, at 1mA cm -2 At the specified current density, in the newly prepared NaBF4-DMSO / NaCl-H2O biphase electrolyte, the utilization rate of the AZ61 magnesium alloy anode can reach 67%, and the energy density can reach 2020 Wh / kg. -1 In a NaCl-H2O single electrolyte solution, the utilization rate of the AZ61 magnesium alloy anode is only 50%, and the energy density is only 1617 Wh / kg. -1 This is because, in the NaBF4-DMSO organic electrolyte, the hydrogen evolution side reaction of the AZ61 magnesium alloy anode can be effectively suppressed during discharge, thus significantly increasing its utilization rate.
[0062] Example 2
[0063] Weigh out 15g of NaBF4, 10g of NaCl, 85g of DMF and 90g of deionized water. Dissolve NaBF4 and NaCl in DMF and deionized water respectively for later use.
[0064] The novel biphase electrolyte system uses NaCl-H2O as the cathode electrolyte and NaBF4-DMSO as the anode electrolyte.
[0065] The mass concentration of NaBF4 is 15%, and the mass concentration of NaCl is 10%.
[0066] The anolyte and catholyte were prepared according to the steps described above. A magnesium-air battery was assembled using the PVDF-SPEEK ion exchange membrane prepared in Example 1 as the separator, an air electrode with MnO2 / C catalyst prepared in Example 2 as the cathode, and AZ61 magnesium alloy as the anode. The prepared battery was then subjected to electrochemical performance testing using the Xinwei Battery Testing System.
[0067] Example 2 uses a method that is basically the same as that in Example 1, except that the solution of the electrolyte at the anode is changed from DMSO to DMF, and the mass concentration of solute NaBF4 is increased from 8% to 15%. Figure 5 This is a SEM image of the surface of AZ61 magnesium alloy after discharge in NaBF4-DMF electrolyte. Figure 5 As can be seen, the surface of AZ61 magnesium alloy is smoother after discharge in NaBF4-DMF electrolyte. This is because the hydrogen evolution side reaction of the AZ61 magnesium alloy anode during discharge can be effectively suppressed in the NaBF4-DMF organic electrolyte. At 1 mA cm⁻¹ -2 At the specified current density, in the novel NaBF4-DMF / NaCl-H2O biphase electrolyte, the utilization rate of the AZ61 magnesium alloy anode can reach 67% (same as in Example 1), and the average discharge voltage is 1.40V (1.40mW / cm²). -2 The energy density can reach 2063.6 Wh / kg. -1 . Figure 6 This is a SEM image of the surface of AZ61 magnesium alloy after discharge in NaCl-H2O electrolyte. Figure 6 It can be clearly seen that the surface of the AZ61 magnesium alloy anode is rough after discharge, and a large amount of Mg(OH)2 is generated. This indicates that the AZ61 magnesium alloy anode has a serious hydrogen evolution side reaction during discharge in NaCl-H2O electrolyte, resulting in its low utilization rate.
[0068] Example 3
[0069] Weigh out 12g of KBF4, 10g of NaCl, 88g of DMSO and 90g of deionized water. Dissolve KBF4 and NaCl in DMSO and deionized water respectively for later use.
[0070] The novel biphase electrolyte system uses NaCl-H2O as the cathode electrolyte and KBF4-DMSO as the anode electrolyte.
[0071] The mass concentration of KBF4 is 12%, and the mass concentration of NaCl is 10%.
[0072] The anolyte and catholyte were prepared according to the above steps. A magnesium-air battery was assembled using the PVDF-SPEEK ion exchange membrane obtained in Preparation Example 1 as the separator, an air electrode with MnO2 / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode. The prepared battery was then subjected to electrochemical performance testing using the Xinwei Battery Testing System.
[0073] Example 3 uses essentially the same method as Example 1, except that the mass concentration of the solute KBF4 in the electrolyte at the anode is increased from 8% to 12%. At 1 mA cm⁻¹ -2 At the specified current density, in the newly prepared KBF4-DMSO / NaCl-H2O biphase electrolyte, the utilization rate of the AZ61 magnesium alloy anode was 67%, and the average discharge voltage was 1.35V (1.35mW / cm²). -2 The energy density reaches 1989.9 Wh / kg. -1 The electrolyte used is essentially the same as that used in Example 1. This is because, in the KBF4-DMSO organic electrolyte, KBF4 and NaBF4 have the same function; different concentrations only slightly affect their conductivity. During discharge, the hydrogen evolution side reaction of the AZ61 magnesium alloy anode can be effectively suppressed.
[0074] Comparative Example 1
[0075] Weigh 10g of NaCl and 90g of deionized water, and dissolve the NaCl in the deionized water to prepare an aqueous solution of NaCl for later use.
[0076] The NaCl electrolyte has a mass concentration of 10%.
[0077] Using the NaCl solution prepared according to the above steps as the electrolyte, an air electrode with MnO2 / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The electrochemical performance of the prepared battery was then tested using the Xinwei Battery Testing System.
[0078] Test results are as follows Figure 3 and 4 As shown, in a 10% NaCl single electrolyte, the utilization rate of the AZ61 magnesium alloy anode is only 50%, and the energy density is only 1617 Wh / kg. -1 This is because AZ61 magnesium alloy suffers from severe hydrogen evolution corrosion in NaCl aqueous solution, which greatly reduces its discharge utilization rate.
[0079] Comparative Example 2
[0080] Weigh 15g of NaBF4 and 85g of DMSO, and dissolve NaBF4 in DMSO ions to prepare a NaBF4 / DMSO solution for later use.
[0081] The mass concentration of NaBF4 is 15%.
[0082] Using the NaBF4 / DMSO solution prepared according to the above steps as the electrolyte, an air electrode with MnO2 / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The prepared battery was then subjected to electrochemical performance testing using the Xinwei Battery Testing System.
[0083] The discharge test results showed that the battery could not discharge normally. This is because the air cathode of the magnesium-air battery requires water to participate in the reaction during discharge. In the NaBF4 / DMSO organic solution, water does not have discharge activity, resulting in the battery's inability to discharge normally.
[0084] Comparative Example 3
[0085] Weigh 10g of NaCl, 20g of DMSO and 70g of deionized water. Dissolve NaCl in a mixed solution of deionized water and DMSO to prepare a NaCl / H2O / DMSO solution for later use.
[0086] The NaCl mass concentration is 10%, the DMSO mass concentration is 20%, and the H2O mass concentration is 70%.
[0087] Using the NaCl / H₂O / DMSO solution prepared according to the above steps as the electrolyte, an air electrode with MnO₂ / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The electrochemical performance of the prepared battery was then tested using the Xinwei Battery Testing System.
[0088] Discharge test results showed that the battery's discharge performance was lower than that of the magnesium-air battery using NaCl as the single electrolyte. This is because the addition of DMSO reduced the electrolyte's conductivity, leading to a decrease in the battery's discharge voltage. Simultaneously, the presence of a large amount of water prevented a significant improvement in the utilization rate of the magnesium anode.
[0089] Comparative Example 4
[0090] Weigh 10g of NaCl, 30g of DMF and 60g of deionized water. Dissolve NaCl in a mixed solution of deionized water and DMF to prepare a NaCl / H2O / DMF solution for later use.
[0091] The NaCl has a mass concentration of 10%, the DMF has a mass concentration of 30%, and the H2O has a mass concentration of 60%.
[0092] Using the NaCl / H₂O / DMF solution prepared according to the above steps as the electrolyte, an air electrode with MnO₂ / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The electrochemical performance of the prepared battery was then tested using the Xinwei Battery Testing System.
[0093] Discharge test results showed that the battery's discharge performance was lower than that of the magnesium-air battery using NaCl as the single electrolyte. This is because the addition of DMF reduced the electrolyte's conductivity, leading to a decrease in the battery's discharge voltage. Simultaneously, the presence of a large amount of water prevented a significant improvement in the utilization rate of the magnesium anode.
[0094] Comparative Example 5
[0095] Weigh 10g of NaBF4, 20g of DMSO and 70g of deionized water, dissolve NaBF4 in a mixed solution of deionized water and DMSO to prepare a NaBF4 / H2O / DMSO solution for later use.
[0096] The NaBF4 mass concentration is 10%, the DMSO mass concentration is 20%, and the H2O mass concentration is 70%.
[0097] Using the NaBF4 / H2O / DMSO solution prepared according to the above steps as the electrolyte, an air electrode with MnO2 / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The electrochemical performance of the prepared battery was then tested using the Xinwei Battery Testing System.
[0098] Discharge test results show that the anode utilization rate of magnesium-air batteries using this electrolyte is lower than that of magnesium-air batteries using NaCl electrolyte. This is because NaBF4 hydrolyzes in aqueous solution to produce acidity, and in this environment, the hydrogen evolution side reaction at the magnesium anode increases significantly.
[0099] Comparative Example 6
[0100] Weigh 10g of NaBF4, 30g of DMF and 60g of deionized water, dissolve NaBF4 in the mixed solution of deionized water and DMF to prepare a NaBF4 / H2O / DMF solution for later use.
[0101] The NaBF4 mass concentration is 10%, the DMF mass concentration is 30%, and the H2O mass concentration is 60%.
[0102] Using the NaBF4 / H2O / DMF solution prepared according to the above steps as the electrolyte, an air electrode with MnO2 / C catalyst obtained in Preparation Example 2 as the cathode, and AZ61 magnesium alloy as the anode, a magnesium-air battery was assembled. The prepared battery was then subjected to electrochemical performance testing using the Xinwei Battery Testing System.
[0103] Discharge test results show that the anode utilization rate of magnesium-air batteries using this electrolyte is lower than that of magnesium-air batteries using NaCl electrolyte. This is because NaBF4 hydrolyzes in aqueous solution to produce acidity, and in this environment, the hydrogen evolution side reaction at the magnesium anode increases significantly.
[0104] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A magnesium-air battery electrolyte, characterized in that, The magnesium-air battery electrolyte is a two-phase electrolyte, comprising an anolyte and a catholyte; The anolyte is an organic electrolyte; The cathode electrolyte is an inorganic electrolyte; The organic electrolyte comprises an anolyte and solvent I; The anode electrolyte is fluoroborate; The solvent is selected from at least one of dimethyl sulfoxide and N,N-dimethylformamide; The inorganic electrolyte comprises a cathode electrolyte and solvent II; The cathode electrolyte is selected from at least one of sodium chloride, potassium chloride, sodium sulfate, potassium sulfate, and sodium formate. Solvent II is water.
2. The magnesium-air battery electrolyte according to claim 1, characterized in that, The fluoroborate is selected from at least one of sodium fluoroborate, potassium fluoroborate, and ammonium fluoroborate.
3. The magnesium-air battery electrolyte according to claim 1, characterized in that, The mass concentration of the anolyte in the anolyte is 5% to 20%. The mass concentration of the cathode electrolyte in the cathode electrolyte is 2% to 15%.
4. A magnesium-air battery, characterized in that, The magnesium-air battery includes an anode, a cathode, and a separator for separating the anode and the cathode. The cavity between the anode and the separator is filled with an anolyte, and the cavity between the cathode and the separator is filled with a cathode electrolyte. The anolyte is selected from the anolyte of the magnesium-air battery electrolyte according to any one of claims 1 to 3; The cathode electrolyte is selected from the cathode electrolyte of the magnesium-air battery according to any one of claims 1 to 3.
5. The magnesium-air battery according to claim 4, characterized in that, The anode is a magnesium alloy.
6. The magnesium-air battery according to claim 4, characterized in that, The cathode is selected from at least one of the following: a porous air electrode supported on MnO2 / C catalyst, a porous air electrode supported on Ag / MnO2 catalyst, and a porous air electrode supported on MnO2 / carbon nanotubes.
7. The magnesium-air battery according to claim 4, characterized in that, The membrane is selected from at least one of PVDF-SPEEK ion exchange membrane, Nafion 115, and polyaniline.
8. The magnesium-air battery according to claim 4, characterized in that, The anode utilization rate of the magnesium-air battery is 60%~80%.
9. The magnesium-air battery according to claim 4, characterized in that, The discharge voltage of the magnesium-air battery is 0.1~1.8V; The power density of the magnesium-air battery is 1.2 mW / cm². -2 ~11.5 mW cm -2 .
Citation Information
Patent Citations
Composite corrosion inhibitor electrolyte, application thereof and magnesium air battery
CN110364787A
Electrolyte for efficiently regulating and controlling dissolution behavior of magnesium anode and preparation method of electrolyte
CN114759294A